PENGARUH PENGENDALIAN INTERNAL TERHADAP NON PERFORMING FINANCING PEMBIAYAAN MUDHAROBAH - Abdul Manan (Universitas Budi Luhur, 2024)
This study aims to analyze internal control over financing risk or Non Performing Financing (NPF) in mudharabah contracts, with a quantitative approach. The population in this study is Islamic Microfinance Institutions in Semarang City, Central Java. The sample of this study was 50 respondents. This study used purposive sampling. The dependent variable of this study is NPF. While the independent variables in this study are qualified employees, healthy practices and reliability of financial reports, good organizational structure. The statistical analysis method used in this study uses multiple regression. The results of this study indicate that employee quality variables have a significant influence on NPF, practice and financial report variables have an effect on NPF, and organizational structure variables have no effect on NPF. This study provides insight for Islamic Microfinance Institutions that adequate internal control can reduce the NPF level in mudharabah financing.